2014
DOI: 10.1111/sjop.12149
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted reading intervention with a phonics approach for children using cochlear implants or hearing aids

Abstract: The present study examines computer-assisted reading intervention with a phonics approach for deaf and hard of hearing (DHH) children in Sweden using cochlear implants or hearing aids, or a combination of both. The study included forty-eight children, 5, 6 and 7 years of age. Sixteen children with normal hearing (NH) served as a reference group. The first purpose of the study was to compare NH and DHH children's reading ability at pre and post intervention. The second purpose was to investigate effects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…The error decoding analysis showed that children with CI made far more phoneme deletions in decoding than NH children. These results may suggest that less fine-grained phonological processing skills in children with CI may hamper the use of the phonological route, explicitly used in nonword decoding (Nakeva von Mentzer et al, 2014). Similar conclusions were recently drawn in a study of reading and spelling skills in children with mild to moderate hearing loss (Park et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…The error decoding analysis showed that children with CI made far more phoneme deletions in decoding than NH children. These results may suggest that less fine-grained phonological processing skills in children with CI may hamper the use of the phonological route, explicitly used in nonword decoding (Nakeva von Mentzer et al, 2014). Similar conclusions were recently drawn in a study of reading and spelling skills in children with mild to moderate hearing loss (Park et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…Sessions pre and post intervention included the same 8 tests as at B1 as well as tests for visual and complex working memory and reading. Results regarding intervention effects on the eight tasks for PhPS and letter knowledge are reported in a previous study [17], and for reading in a second study [57]. Children were given one pause after half of the tests.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…The program demonstrates how to blend isolated sounds into syllables and words and, thus, offers basic exercises for spelling [37]. Graphogame has a child friendly design to keep children's motivation high, for example they may choose their own favourite game character, a princess, an animal, or a knight, and after each level of difficulty they are rewarded with tokens presented in another background, for example a castle or a garden.One special game is the ghost-and-ladder game where children make the ghost climb up the ladder when giving correct responses [55][56][57].…”
Section: Intervention Program and Settingmentioning
confidence: 99%
“…Only one study explicitly reported the participation of post-lingual deaf individuals 26 . Hearing individuals participated in interventions reported by seven studies [27][28][29][31][32][33]36 . Some of these studies, such as the publications from Suskind et al 33 and Clare Allen et al 31 aimed to establish teaching repertoires or increase the number of words and the quality of statements emitted in the context of the deaf and CI user child -thus, creating conditions for the occurrence of incidental learning of these repertoires.…”
mentioning
confidence: 99%
“…Seven studies had more than 21 participants 13,[29][30][31][32][33][34] , in which three publications 29,31,33 had hearing participants as direct target of the interventions (e.g., parents, teachers and CI users caretakers) aiming to evaluate its indirect effects on deaf children and CI users' rehabilitation. Two studies were characterized as case studies and only one individual participated of each 35,36 .…”
mentioning
confidence: 99%